Introducción al estudio comparativo de los idiomas japonés y el coreano - Guerrero Plaza, Raúl (Historia y Comunicación Social, 2007)
Korean and Japanese are two languages of two very close countries and, at the same time, heavily confronted due to their historic and political relation. Japan and Korea have represented for a long time the antagonism in Asia, and Japan’s colonial ambitions over Korea were fulfilled at the beginning of the 20th century, when it took political and cultural control over Korea for over three decades. During the colonial period, the Korean language, one of the few known languages linked to the Japanese language for its grammar and historical evolution similarities, was about to disappear due to the cultural pressure imposed by Japan. But this is only the most recent event that related both languages, for the relationship between the two is much older. This article aims to make a historical approach analysis of to the evolution of both Japanese and Korean languages.